Bilanggong Birhen - Tolosa, Carlos Vander; Sampaguita Pictures (Sampaguita Pictures, 2005)
Flora (Amalia Fuentes)comes home only to find that her father is dying. Now that she is left all alone, there is no one to protect her against her covetous stepmother (Etang Discher) and her son Mouriscio (Rod Navarro). the two conspire against Flora, making her life miserable everyday. Before long, she suffers from a nervous breakdown and is taken to asylum. Fidel (Romeo Vasquez), the doctor who looks after Flora becomes very interested in her. When Flora gets well, Fidel proposes marriage to her. Unfortunately Flora's stepmother is able to trace where she lives and takes her back home. With just days till her marriage to Mauricio, will Flora ever manage to break away from the wicked hold of her stepmother and her son?